Polymorphism of CSN2 Gene Exon 7 in Indonesian Dairy Goat Breeds - Gisela Deviandini; Ronny Rachman Noor; Epi Taufik; Santiananda Arta Asmarasari (Buletin Peternakan, 2023)
Milk production and composition are the main factors in the dairy industry. However, these traits are influenced by several factors, such as genetic factors. The CSN2 gene exon 7 is one of the genes that can affect the protein composition of goat milk. Several studies on the CSN2 gene exon seven have been conducted on Italian and Indian goat breeds, and their genetic variations have been found. Studies about CSN2 gene exon seven polymorphisms in Indonesia have been completed but found no variations. Therefore, this study aims to find genetic variations of CSN2 gene exon 7 using the Sanger Sequencing Method. Ninety-five blood samples of 66 Sapera, 15 Saanen, and 14 Etawa Grade goats were collected from the Livestock Research Center, Ciawi. Genetic diversity was calculated using PopGene32 programs. The results found two polymorphic SNPs in all three dairy goat breeds, namely g.8946C>T and g.8956G>A. Three genotypes found in SNP g.8946C>T are CC, CT, and TT, while a new SNP g.8956G>A found two genotypes (GG and GA). In conclusion, SNPs g.8946C>T and g.8956G>A are polymorphic. Additional research should be conducted to determine whether there is any association between these 2 SNPs and milk production and quality.